Formulasi Dan Evaluasi Fisik Lipstik Dari Ekstrak Kulit Umbi Bit (Beta vulgaris L.) - Eryani, Mikhania Christiningtyas; Aditama, Agnis Pondineka Ria; Husni, Patihul; Permatasari, Lina Putri (JURNAL FARMASI GALENIKA, 2025)
Lipstick is a cosmetic used to add color to the lips. Natural dyes that can be used as a lipstick component are beet (Beta vulgaris L.) skin extract. The skin of beet contains betacyanin which can give color to the lips. This study aims to determine the effect of varying concentrations of beet skin extract on the physical properties of lipstick. There are 3 lipstick formulas used with a 1% (F1), 2% (F2), and 3% (F3) concentration of beet skin extract. The research results show that F1 is pink, F2 is red, and F3 is dark red. The entire formula has even spreadability. The pH values of F1, F2, and F3 are 4.9±0.173, 5±0.3, and 5.3±0, respectively. The melting points of F1, F2, and F3 are 50.66±1.15°C, 52.66±1.15°C, and 53.66±0.58°C, respectively. The conclusion of this study is that variations in the concentration of beet extract affect the color, pH, and melting point of lipstick but do not affect the spreadability of lipstick.